Central Giant cell injury in the mandibular symphysis of a pediatric patient: case report (Research, Society and Development, 2021)
The central lesion of giant cells (LCCG) is a non- neoplastic bone lesion that affects gnathic bones in patients from early childhood to the elderly, being more prevalent between the second and third decade of life and in females. It should be taken in to account that, in general, head and neck tumors in childhood generally demonstrate an atypical biological risk. However, the LCCG shows a variety of aggressive and non- aggressive behavior, thus acting directly on the established treatment. In pediatric patients with mixed dentition, a pathological lesion can be the underlying cause of tooth mobility and exfoliation of primary teeth and can be easily ignored, especially in cases that are not accompanied by a classic bone expansion. The present study aims to report a case of an 11 years old male child who, in the orthodontic evaluation, reported sensation in the mandibular teeth that would have been changing positions for approximately two months, without pain and with hypoesthesia in the lower lip. Computed tomography and incisional biopsy were performed to confirm the diagnosis and, subsequently, enucleation was performed followed by peripheral osteotomy under general anesthesia. It was concluded that the pathology is uncommon and has an unknown etiology. It is clear that, despite having benign biological behavior, it can be highly destructive, enabling different forms of surgical procedures. Its definitive diagnosis depends on evaluations through the analysis of clinical, radiographic, histopathological and serological exams, for an individualized approach within the presented clinical picture, similar to this report.